Who Represents the Constituency? Online Political Communication by Members of Parliament in the German Mixed-Member Electoral System - Lennart Schürmann; Sebastian Stier (Legislative Studies Quarterly, 2023)
Members of parliament (MPs) are elected via two different tiers in mixed-member electoral systems—as winners of a seat in a constituency or as party candidates under proportional rules. While previous research has identified important consequences of this “mandate divide” in parliaments, questions remain how this institutional setup affects MPs' political behavior in other arenas. Analyzing more than one million social media posts, this article investigates regional representation in the online communication of German MPs. The results show that MPs elected under a direct mandate refer approximately twice as often to their constituencies by using regionalized wording and geographic references than MPs elected under the proportional tier. The substantive findings provide new evidence for the benefits of mixed-member electoral systems for political representation while the methodological approach demonstrates the added value of social media data for analyzing the political behavior of elites.
Keywords: 320